2018
DOI: 10.3233/wor-182815
|View full text |Cite
|
Sign up to set email alerts
|

Study-related mental health symptoms and their correlates among allied health professions students

Abstract: BACKGROUND: Allied health professions (AHP) students are subject to critical levels of study-related stressors including mental health symptoms (MHS) and musculoskeletal pain. Few studies recruited AHP students of multiple academic majors simultaneously. OBJECTIVES: This study investigated and compared the prevalence of MHS severity and their associated factors among students of nine AHP majors. METHODS: A cross-sectional design was used with a sample of nine AHP academic majors (n = 838). Participants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 64 publications
3
16
0
5
Order By: Relevance
“…14,16,17 The Arabic version of the questionnaire showed to be valid and reliable. 18 22,23 The test score ranges between 0 and 21 points for each subscale where a higher score indicates a higher level of mental health symptoms. The cut-off points score is nine for depression, seven for anxiety and 14 for stress, with higher scores indicating severe symptoms.…”
Section: • • the Oswestry Disability Index Was Used Tomentioning
confidence: 99%
“…14,16,17 The Arabic version of the questionnaire showed to be valid and reliable. 18 22,23 The test score ranges between 0 and 21 points for each subscale where a higher score indicates a higher level of mental health symptoms. The cut-off points score is nine for depression, seven for anxiety and 14 for stress, with higher scores indicating severe symptoms.…”
Section: • • the Oswestry Disability Index Was Used Tomentioning
confidence: 99%
“…DASS-21 normal cut-off scores are nine for depression, seven for anxiety, and 14 for stress, scores exceeding these cutoffs are labeled as mild, severe, or extremely severe on corresponding symptom with higher scores suggesting more severe symptoms (Crawford and Henry 2003). DASS-21 is validated for the Arabic language and has shown high validity, reliability, and internal consistency (Cronbach alpha range 0.78-0.91) (Brown et al 1997;Ali et al 2017;Almhdawi et al 2018).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Previous research has shown that students from lower SES backgrounds tend to be less satisfied than students from higher SES backgrounds with their university experience (Martin 2012). In addition, satisfaction with university is positively related to students' mental health (e.g., Almhdawi et al 2018;Karaca et al 2019). Hence, it may be useful to control for satisfaction at university when investigating the association between subjective social status and mental health.…”
Section: Control Variablesmentioning
confidence: 99%